Production systems and strategies of peri-urban goat and sheep farmers for dry season feeding: a case study from Benin (West-Africa) - Bossima Ivan Koura; Fifame Panine Yassegoungbe; Luc Hippolyte Dossa (Cogent Food & Agriculture, 2024)
This study was conducted to understand the urban small ruminant production system in the peri-urban area of southern Benin and investigate farmers’ feeding strategies in the dry season. One hundred and twenty-five (125) farms were interviewed (survey n°1) in five urbanized municipalities, using a semi-structured questionnaire on their socio-economic characteristics and production strategies, including their feeding practices. A typology of small ruminant farm types was implemented, and the farm types were characterized. Then, the feeding strategies were investigated in-depth in the most urbanized sub-area (Abomey-Calavi) on 120 farms (survey n°2). In addition, for 03 months in the dry seasons, thirty (30) farms were monitored in the municipality of Abomey-Calavi to assess the diversity of feed resources used. Six small ruminant farming systems were identified throughout the five municipalities. Goat farms were more common than sheep farms. Free grazing on communal grazing lands was the primary forage source, with supplementation provided on all farms. However, the feed supplementation strategies varied between farm types. Feed resources used included tree fodders (Manihot esculenta, Elaeis guineensis, Musa spp., Gliricidia sepium) or agro-industrial by-products (corn bran, soybean bran, cassava peels) in all farm types, and crop residues mainly in SC and SGC when they were available. Variations were observed (p < 0.001) in feeding strategies across farm types in the dry season. Improving animal nutrition by increased recycling of food or vegetable wastes and agro-industrial by-products from the city fringes appears to be an essential factor in enhancing the sustainability of periurban farms.